Selection of patients by dentists in a situation where health resources are scarce - d’Ávila, Sérgio; Leite Cavalcanti, Alessandro; Caldas JR, Arnaldo de França (Acta Bioethica, 2012)
To identify which criteria influenced the selection of patients by dentists in a city of Northeastern Brazil. A cross-sectional study was carried out by collecting data through a questionnaire, consisting of identification data and a case scenario, 308 respondents had to choose, by looking at photos of six supposed patients, the only one who should receive emergency dental treatment in a situation of scarce health resources. The absolute and percent frequencies were obtained for data analysis (descriptive statistical techniques). For the selection of the six patients, the most frequently chosen patient was the 50 year old white male (70.5%) followed by the female of African descent (12%). The dentist’s gender did not have a statistically significant effect on the choice of the patient (P=0.3366). Age was the most relevant criterion for the choice (46.4%) followed by the patient’s physiognomy (30.8%). There was no significant difference between age and choice of the patient (P=0.8133). However, there was a significant association between age and reason of choice (P=0.0258). Subjective criteria interfered in the choice: the first impression caused by different physical features.